Studi Deskriptif Tentang Penggunaan Model Teaching Games For Understanding (Tgfu) dalam Pembelajaran Passing Bola Voli di SMPN 02 Ella Hilir - Widi Kurniawan; Eko Rudiansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the implementation of the Teaching Games for Understanding (TGFU) learning model in teaching passing techniques in volleyball within Physical Education, Sports, and Health learning at SMPN 02 Ella Hilir. The method used was a descriptive method with a qualitative approach. The research subjects consisted of 12 ninth-grade students. Data were collected through observation, interviews, and documentation to obtain an overview of the learning process. The results showed that the implementation of the Teaching Games for Understanding (TGFU) model could improve students’ activity and engagement in the volleyball learning process. Through game-based learning, students became more active, enthusiastic, and better able to understand game concepts and the execution of passing techniques. However, several obstacles were still found, such as incorrect ready position, lack of coordination between hand movements and visual focus on the ball, and improper control of force when performing passing. In conclusion, the Teaching Games for Understanding (TGFU) model can be an effective alternative learning model in volleyball learning, especially in teaching passing techniques. Keywords: Physical Education, Passing, Teaching Games for Understanding, Volleyball